Multinational Corporations from Emerging Markets
XVIII, 232 p.
Keywords: The rise of multinational corporations (MNCs) from emerging markets has been a major development during the last decade. An important feature of emerging market MNCs is their close relationship with home states. The book investigates this special kind of relationship and explores how it affects the cross-border activities of these corporations.